THE PROBLEMS OF INTERCULTURAL COMMUNICATION ON THE EXAMPLE OF GREETING FORMS PECULIARITIES IN AUSTRIA AND GERMANY - T. A. Yakovleva (Концепт: философия, религия, культура, 2017)
This article discusses the forms of greeting in the modern literary language of Germany and Austria and justifies the necessity of their study to prevent misunderstandings in the process of interaction between two cultures. The introduction emphasizes the importance of intercultural communication and indicates the causes of communicative barriers. The article substantiates the relevance of the research topic, which is due to the need for confrontative research of the multivariate languages’ national variants. The main task of the study is to analyze the characteristics of the formation, pronunciation and use forms of greetings in speech. The greeting is of great importance for successful communication and is not an empty formality. It performs various functions: communicating, norms of civility, the impact on the interlocutor. There are many forms of greetings and treatment, such as verbal and non-verbal, which often complement each other. The German language is very diverse and there are many ways to say hello and goodbye. A common language not only binds, but also divides the Austrians and Germans. There are some unique forms of greeting in the Austrian and in the German national variant. They have their own interesting history and there are certain application rules. In order to escape an awkward situation, you must be aware of etiquette adopted in the country. The results of this study may be of interest for using in courses of regional geography in German-speaking countries and in teaching practice.